CONTROVERSY OF EQUAL RIGHTS TO THE APPLICATION OF THE DEATH PENALTY TO EXTRA ORDINARY CRIME PERSPECTIVE PANCASILA WITH JUSTICE - Billy Pahlevy Islamy; Nurdin Nurdin; Dominikus Rato; I Gede Widhiarna Suarda; Bayu Dwi Anggono (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2025)
This study explores the controversy surrounding the application of the death penalty to perpetrators of extraordinary crimes from the perspective of Pancasila, which upholds the principles of civilized justice. Although the death penalty is officially regulated in the Criminal Code and sectoral laws related to narcotics, terrorism, and corruption, its practice shows inconsistencies. The state strongly enforces the death penalty for drug and terrorism offenders but is more lenient toward corruption offenders, even though the law allows the death penalty under certain circumstances. This disparity raises concerns about potential abuse of power, violates the principle of equality before the law, and undermines public trust in the legal system. The research employs a qualitative method with a normative legal approach, analyzing laws and regulations, doctrines, court decisions, and relevant academic literature. The analysis is conducted descriptively and analytically, with Pancasila used as an evaluative framework. The findings emphasize the need for consistent application of the death penalty for all extraordinary crimes to ensure that the law upholds substantive justice. Using Pancasila as a benchmark, the state is expected to enforce the law in an equitable, accountable, and fair manner, so that the death penalty serves as an instrument of justice rather than a tool of power.